Kisi Difraksi Sederhana Berbasis Alam : Bawang Daun (Allium fistulosum) dan Jantung Pisang (Musa paradisiaca) (UPEJ Unnes Physics Education Journal, 2021)
Diffraction is one of the properties of light in the form of a bending event in the direction of the propagation of the waves through a narrow gap. Research on natural materials as an alternative to grating has been carried out with varying results. Natural ingredients in the form of scallion stems (Allium fistulosum) and banana heart (Musa paradisiaca) were chosen as the diffraction lattice preparations because they have fibers that resemble scratches on the diffraction grating produced by factories. Special care is given to each preparation to obtain the fiber. By using Tracker and analysis of the level of accuracy, the results obtained value m, and an accuracy of 95.81% for the diffraction grating of scallion stems, and the value of d = and accuracy of 90.01%. The results of this study indicate that scallion stalks and banana blossoms have potential and can be used as diffraction grating to explain light diffraction phenomena.